Photodynamic therapy as adjunctive therapy for morpheaform basal cell carcinoma - Torres, Tiago (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
The authors decided to evaluate the possible use of methyl-aminolevulinate photodynamic therapy (MAL-PDT) as adjunctive therapy for morpheaform basal cell carcinoma prior to standard surgical excision in order to reduce tumor size and volume and to facilitate surgical treatment. It was observed that MAL-PDT may be an option as an adjunctive therapy prior to standard surgical excision of morpheaform basal cell carcinoma, leading to less invasive surgery.
Keywords: dermatologija; fotodinamično zdravljenje; karcinom; therapy; zdravljenje